PENGARUH PENDEKATAN PENCAPAIAN KONSEP TERHADAP PEMAHAMAN KONSEP MATERI BENTUK MOLEKUL DI SMA - Ayni, Ayni; Muharini, Rini; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstarctThe purpose of this study was to determine the effect of concept attainment approach with conceptual change text on molecular shape materials toward the learning outcomes of students SMAN 1 Sungai Pinyuh. Research form was a quasi-experimental research design with non equivalent control group pretest-postest design. The sampling method used purposive sampling, where the X MIPA 2 class was chosenÂ as an experimental class and the X MIPA 3 class as the control class. Data collectionâ€™s tool used the achievement test in the form of an short answer. Test result by U-Mann Whitney (=0,05) obtained significant 0,000, indicating that there was a difference between the learning outcomes of student who were tought using a concept attainment approach with conceptual change text and students be taught by conventional methode in the molecular shape materials. Concept attainment approach with conceptual change text gave a high influence with effect size value by 1,48. Therefore concept attainment approach with conceptual change text influence students learning outcomes by 56.78%.Â Keyword: Concept Attainment Approach, Conceptual Change Text, Learning Outcomes